Nilai-Nilai Islami pada Soft Skill - Aries Musnandar; Abdillah Ubaidi (Jihbiz : Jurnal Ekonomi, Keuangan dan Perbankan Syariah, 2022)
The Islamic value's substance is actually humankind's noble behaviors, as practiced by the Prophet in his daily life. This study constitutes the main discussion of Islamic values' conceptual and theoretical framework on soft skills. Globally, the term soft skills are introduced and popularized in West Countries by people with no Islamic worldview. This study focuses on elaborating the concept of soft skills (SS) from the Islamic perspective. According to the Islamic viewpoints, the best righteous people are those who can contribute to others through their good deeds. In the society era 5.0, possessing competent human capital is crucial for a Country. This research reviews the precept of al Quran and Hadith as the primary sources of Islamic values in developing the personal quality of Muslims. The study employs a qualitative research method with a literature study design, meaning making through interpretation of the Holy Quran and the Prophet traditions (Hadith). Based on findings, it is known substantively that the Islamic teachings are comprehensive concepts to build and shape the noble behavior of Muslims. Eventually, the researcher offers soft skills formula from an Islamic perspective as a complete concept for creating an excellent personality. Soft skills in the Islamic perspective are morals, good morals, positive behavior, spreading goodness, and bringing many benefits.